Microassembly on silicon board for accelerometer - Spirin V. G. (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature, 2013)
The paper presents microassembly design and technology for accelerometer, carried out on a silicon plate with three commutation levels and thin film resistors on both of its surfaces.